Integration Green Supply Chain Management and Environmental Consciousness: Direct Effects Sustainability Performance - Rizki, Adam Firman; Murwaningsari, Etty; Sudibyo, Yvonne Augustine (IJOSMAS, 2022)
Purpose this research to determine the effect of the nine dimensional constructs of GSCM and Environmental Consciousness on sustainability performance. This study is a quantitative study that has a sample of 483 manufacturing companies in Indonesia. The data used are primary data obtained by distributing questionnaires to the middle up managers of the company. From the research results, it is known that Green Purchasing, Green Marketing, Green Manufacturing and Green Design as four constructs of GSCM and Environmental Consciousness have an influence on the company's sustainability performance. Eco-design, Intern Environmental Management, Environmental Education, Customer Cooperation, Green Information System haven’t effect to sustainability performance. This research able to be a guide for practitioners in supply chain field and also company management in an effort to company’s achievement of sustainability performance. This study has not discussed about integration information systems and the risks that may arise from environmentally friendly supply chain processes.